2018
DOI: 10.1007/s12639-018-1029-4
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, isolation, molecular detection and genetic diversity of Toxoplasma gondii from small ruminants in Egypt

Abstract: Toxoplasmosis is an infectious zoonotic disease caused by protozoan Toxoplasma gondii. Detection of T. gondii infection with touchy and particular strategies is a key advance to control and prevent toxoplasmosis. Genotyping can explain the virulence, epidemiology and setting up new methodologies for diagnosis and control in human and animals. The point of this study was to assess the seroprevalence of T. gondii in sheep and goat in Egypt and to comprehend the genetic variety of T. gondii isolates circling in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
3
6
2
Order By: Relevance
“…Our results were relatively higher than those reported in different areas in Egypt 28.1% at Cairo by ELISA(Abd El-Razik et al, 2018;Abbas et al, 2019), and 32.0%(El- Gawady et al, 2018). Our result was lower than another finding in Egypt as in Dakahlia 50.6%(Younis et al, 2015), 59.0% and 54.0% (Al-Kappany et al, 2018) by using ELISA and IFA, respectively and 43.0% documented at Cairo, Giza, Kalubyia using ELISA(El-Fadaly et al, 2017).…”
contrasting
confidence: 72%
“…Our results were relatively higher than those reported in different areas in Egypt 28.1% at Cairo by ELISA(Abd El-Razik et al, 2018;Abbas et al, 2019), and 32.0%(El- Gawady et al, 2018). Our result was lower than another finding in Egypt as in Dakahlia 50.6%(Younis et al, 2015), 59.0% and 54.0% (Al-Kappany et al, 2018) by using ELISA and IFA, respectively and 43.0% documented at Cairo, Giza, Kalubyia using ELISA(El-Fadaly et al, 2017).…”
contrasting
confidence: 72%
“…In addition, our results are consistent with other reports in Pakistan and Spain, where the seropositivity rates of T. gondii in the examined ruminants were 42.80% (107/250) and 42.5% (826/1943), respectively [21,22]. Moreover, a study conducted in Egypt has shown a similar seroprevalence of T. gondii in sheep and goats, with infectivity levels of 46.6% (97/208) and 52.4% (109/208), respectively [23].…”
Section: Discussionsupporting
confidence: 90%
“…To the author’s knowledge, this is the first report of T. gondii oocysts detected directly from cat faeces in Malaysia using both copro-microscopy and copro-PCR techniques. The previous studies conducted in Malaysia on T. gondii in the last decade (2008 to 2018) were mainly serological tests for detection of the presence of antibodies in the blood of humans or animals [ 4 , 5 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Others searched for new innovative diagnostic approaches and vaccine development for T. gondii [ 44 , 45 , 46 , 47 , 48 ], and characterization of T. gondii genotype studies on free-range ducks and wild boars [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%